Legal Implications of the Application of the Principle of Due Diligence on the Extension of the Work Contract of PT Freeport Indonesia - Dewani, Shan Shofi; Susanto, Sela Kartika Maritza; Muzhaffar, Mugits; Wulandari, Wulandari (Devotion : Journal of Research and Community Service, 2026)
The extension of PT Freeport Indonesia's Contract of Work is one of the strategic issues in national mining governance because it concerns legal certainty, investment sustainability, and the state's authority to manage natural resources. In this context, the principle of acting carefully plays an important role as a normative standard that regulates how parties, especially governments and companies, are obliged to exercise prudence in every stage of preparation, evaluation, and decision-making related to contract sustainability. This study seeks to examine how the principle of prudential action is applied in the process of extending PT Freeport Indonesia's Contract of Work and examines the legal consequences that can arise if the principle is ignored. This study uses a normative juridical approach through the analysis of laws and regulations, contract law principles, specific provisions of the mining sector, and relevant contractual documents. The results of the study show that the application of the principle of acting carefully is the basis for ensuring that contract renewal decisions are implemented in an objective, transparent, and oriented manner to the protection of the public interest. Imprecision in the decision-making process has the potential to cause administrative defects, weaken the legitimacy of the contract, reduce legal certainty for investors, and open up room for disputes in the future. Thus, the application of the principle of careful action is not only an indicator of integrity in the contract extension process, but also has direct implications for the validity of government decisions and the legal relationship between the state and PT Freeport Indonesia. This research emphasizes the urgency of strengthening the prudential mechanism as part of mining governance reform in Indonesia.